Slouching towards Calvary: Whereto the national collection? - Genoni, Paul (2001)
This paper provides an overview of recent cooperative collecting activity in Australia, particularly with regard to the concept of a 'national collection'. It considers the reasons for the failure of the Distributed National Collection, including discussion of the roles played by the National Library and libraries operating under the auspices of the Council of Australian University Librarians during the 1990s. It concludes by advocating a way forward with regard to the continued development and implementation of a national collecting agenda.